Pelatihan Make Up Profesional untuk Peningkatan Keterampilan dan Kewirausahaan Masyarakat Lokal Di Desa Jayamukti Cikarang: Pelatihan Make Up Profesional untuk Peningkatan Keterampilan dan Kewirausahaan Masyarakat Lokal Di Desa Jayamukti Cikarang - Suriyanti; Ismasari Nawangsih; Pupung Purnamasari; Sesri Sellina; Donny Maulana (DPPM Universitas Pelita Bangsa, 2025)
Professional Make Up Training for Improving Skills and Entrepreneurship of Local Communities in Jayamukti Village, Cikarang aims to provide knowledge and skills in the field of make-up to the local community in order to improve the quality of life and open up new business opportunities. Jayamukti Village, located in Cikarang, has great human resource potential, but is often limited by access to relevant skills training. This training program is implemented with a practical approach, involving experienced instructors in the field of professional make-up, and materials that are tailored to the needs of the ever-growing beauty market. By participating in this training, participants are expected to be able to master professional make-up techniques that are not only useful for personal needs, but can also be capital to open a business in the beauty sector. In addition, this training is also expected to increase self-confidence, open up new job opportunities, and support the development of sustainable local entrepreneurship in Jayamukti Village. Evaluation of the success of the training showed an increase in participants' skills, as well as a high interest in applying the knowledge gained in independent beauty businesses, which in turn contributed to the local economy.